Neutral density variation from specular meteor echo observations spanning one solar cycle. Issue 19 (1st October 2014) - Stober, G.; Matthias, V.; Brown, P.; Chau, J. L.
Abstract Specular meteor radars have provided essential information about the mesospheric/lower thermosphere (MLT) dynamics. The Canadian Meteor Orbit Radar has been conducting continuous meteor echo observations in a fixed, stable configuration since 2002. Here we present estimates of the neutral air density variations derived from observations of the meteor peak flux altitude. Using a simple model assuming a linear trend and a sinusoidal solar cycle we derived a trend of a decreasing neutral density of 5.8 ± 1.1% per decade at approximately 91 km altitude and an amplitude across the most recent solar cycle, the solar cycle of 2.4 ± 0.7% for solar cycle 23/24. The long‐term trend of decreasing neutral air density in the MLT is in good agreement with the model results from Akmaev et al. (2006).